Analysis of Mathematical Reasoning Abilities Based on Student’s Independent Learning on Straight Line Equation Material - Dewi, Aluh Mustika; Turmuzi, Muhammad; Kurniawan, Eka; Arjudin, Arjudin (Balai Publikasi Indonesia, 2025)
Reasoning ability is a high-level thinking ability in learning mathematics. Mathematical reasoning and mathematics learning are two things that are interrelated and cannot be separated because mathematical material is understood through reasoning, and reasoning can be trained through studying mathematics. To achieve mathematical reasoning abilities in learning, students need adequate behavior, one of which is learning independence. The aim of this research is to analyze mathematical reasoning abilities based on students' independent learning at SMPN 1 Praya Timur on straight line equations. The method used in this research is qualitative research with descriptive methods. The samples in this study were taken randomly based on the class in the population. The class that the researcher took as a sample in this study was class VIII C at SMPN 1 Praya Timur for the 2023–2024 academic year. The results of this study show that subjects with low reasoning abilities are also categorized as having low learning independence. The learning ability of students who are categorized as moderate turns out to be moderate. So, it can be concluded that the relationship between learning independence and reasoning ability is based on high student learning independence, so their reasoning ability is also high. Based on the results of this research, it is hoped that teachers can develop teaching and practice problem-solving questions to improve students' reasoning abilities